PERSPEKTIF DAN PROSPEK KEAHLIAN TEKNIK DAN MANAJEMEN INDUSTRI DI SUMATERA SELATAN - MZ, Hermanto (JURNAL MEDIA TEKNIK, 2011)
ABSTRACTGlobalization have led to higher levels of competition and rivalry in the face of all parties is required for all sources owned empowering efficiently. Globalization clearly brings many challenges, threats and opportunities faced bythe industry and are not directly the responsibility of the profession of Industrial Engineering. Global challenges confronting higher education technology industries in order to be able to follow the direction of development of scienceand capture fast-moving technology along with the demands of the community (including industry) as a higher education service users. Higher education should be able to prepare qualified human resources, and meet the demands andrequirements of competency standards work helpless behavior. Industrial Engineering and Management program is the right answer to meet these demands. The ability of graduate Engineering and Industrial Management inmanaging the system will give him an integral role in the opportunities for exploiting the resources more efficiently.